Role of System Strategic Learning Smart In Sustainability Success of Managing Network e-Business - الخفاجي, نعمة عباس (Journal of Economics and Administrative Sciences, 2020)
Purpose: Determining and identifying the relationships of smart strategic education systems and their potential effects on sustainable success in managing clouding electronic business networks according to green, economic and environmental logic based on vigilance and awareness of the strategic mind.Design: Designing a hypothetical model that reveals the role and investigating audit and cloud electronic governance according to a philosophy that highlights smart strategic learning processes, identifying its assumptions in cloud spaces, choosing its tools, what it costs to devise expert minds, and strategic intelligence.Methodology: Theoretical dilemma of the diagnosis of the knowledge for smart strategic learning systems and sustainable success in managing cloud business networks. It was derived from the fields of strategic learning and electronic business, both thoroughly and deeply. There was a smart, selective review of the contributions of authors in both fields. It was supported by a group of contemporary works that questioned intellectual capital. A strategist, and scientist who has been subject to reading and analysis.The Approach: focusing on investing strategic learning processes that are effective for change with a global horizon to re-invent the human resource minds and achieve added value in competitive electronic cloud environments. It focuses on the essence of the learning process, the principles, supportive processes, and changes in the basic directions of its systems, tools, and applications, to create a focused cloud strategy, implementation, application, and adaptation to a cloud environment. The entrance included a set of rules drawn from the experiences, sayings, and dreams of expert institutions and leading minded consultants, cognition, thinking, intelligence and a will of power, it is an analytical documentary introduction to a hypothetical, integrated model of the idea, analysis, design, philosophy, and application.Type of Research: The research has a qualitative approach that has adopted rooted theoretical mechanisms with ideas, concepts, and content for a hypothetical model. It was subjected to a logical arrangement of building, interpretation, and expectation with learning and sustainability lenses in the light of cloud business spaces.Determinants: Relying on the mental capabilities of cognition, thinking, and governing trends of smart strategic learning systems and the sustainability of the success of the awareness of cloud business networks. The validity of the content and reliability of the proven references provide accuracy, honesty, truthfulness, reading, and extrapolation.Practical impacts: Opening thinking of smart strategic learning systems to build strategic leadership capabilities. Functionalizing sustainability rules mechanisms to manage cloud business networks. Which are research, study, tools for measuring and evaluating the improvement in strategic performance.Social Impacts: Achieving qualitative changes in commitment and strategic patience, and a strategic partnership, the proof of which is cooperation in investing the two fields in the language of intangible resources. The research contributes to the consolidation of its social structure with values, ethics, will, texture, and culture.Authenticity: Raising the argumentative idea of ​​ logic and philosophy with rational lenses, experience, and alignment in order to integrate mechanisms and rules for sustainability and cognitive deep learning in cloud spaces.